Niche Tourism for Autistic Children during a Pandemic - Mochammad Taufik Ramadhan Zain; Ahmad, Fahry (Politeknik Negeri Bandung, 2022)
The COVID-19 pandemic has become a global disaster. All industrial sectors throughout the country were paralyzed by the virus that originated in the city of Wuhan, China. One of them is the travel and tourism industry. The policy of restricting mobility and crowds of people to reduce the spread of COVID-19 has a direct impact on the tourism sector. The travel and tourism business declined sharply in the MSME business and disrupted the employment opportunities in it. This also happened to Shakira Travel and Tourism which is engaged in the travel and tourism business. This business that was founded in 2016 must be able to rack its brain so that its business can continue to run during the pandemic. One of the strategies used by Shakira travel and tourism is through niche tourism targeting tourists with autism. This paper contains how the impact of this pandemic on the Indonesian tourism sector and the policies and strategies used by Shakira Travel and Tourism to survive. The purpose of this article is to provide an overview of the implementation of the Niche Tourism strategy for children with autism disorders carried out by Shakira Travel and Tourism in maintaining the continuity of the company. By using qualitative research methods which describe the actual situation that occurred during the research and combined with theoretical references from both journals and articles related to business strategies during the pandemic.